Secure communication between grid domains based on trust relationships and group keys. (1st September 2010) - Sadhasivam, G. Sudha; Jini, C. Geetha
The grid facilitates coordinated resource sharing and problem solving in dynamic, multi-institutional virtual organisation (VO). Groups within the VO communicate efficiently by multicasting the shared information. Groups within a VO can be dynamic, because users, resources or sites can join or leave a group at any time. In addition, one member may belong to multiple groups simultaneously. In this context, maintaining data privacy against untrusted users is of utmost importance in the grid environment. This necessitates the encryption of information that is transmitted among the grid entities. To preserve security in communication, the multicast information should be encrypted using a group key. The challenges faced in maintaining security in a VO includes dynamic authentication of group members, dynamic creation, updation and distribution of group keys. In view of the challenges, this paper proposes an efficient approach for dynamic group key generation and distribution. This paper also proposes a novel approach for establishing domain to domain communication using trust relationship among the entities. The proposed approaches were implemented, tested and evaluated on GridSim.